Are there any trade-offs between forage provision and the ecosystem service of C and N storage in arid rangelands? - Oñatibia, Gastón Rafael (2015)
Changes in land use often increase the provisioning ecosystem services at the cost of decreasing the regulating services. Thus, the appropriation of primary production to optimize the supply of forage for livestock production may undermine C and N storage, essential to maintain the integrity of ecological systems and the biosphere. The aim of this work was to study this trade-off by estimating the effect of grazing intensity on two provisioning and regulating ecosystem services (forage supply and C and N storage, respectively) in a 300 km2 Patagonian steppe. In areas with different historical sheep grazing regime (intensive, moderate and ungrazed), we estimated forage supply through the aboveground biomass of preferentially consumed species as well as total C and N storage in plants, through forage and non-forage aboveground biomass, litter and root biomass in the top 20 cm of soil. We found that forage supply and C and N storage were highest in moderately grazed areas and were positively correlated, indicating the absence of trade-offs between them. Grazing exclusion had no effect on total plant C and N, but decreased these stocks in green grass biomass in relation to moderate grazing. Intensive grazing decreased both provisioning and regulating services, markedly diminishing grass C and N stocks and grass forage compared to other conditions. Conversely, shrubs and roots were not influenced by grazing regime. This study provides evidence that in arid rangelands, an adequate grazing management could be a key control to complementarily maximize both provisioning and regulating ecosystem services.